Simulated microgravity disarms human NK-cells and inhibits anti-tumor cytotoxicity in vitro. (September 2020) - Mylabathula, Preteesh Leo; Li, Li; Bigley, Austin B.; Markofski, Melissa M.; Crucian, Brian E.; Mehta, Satish K.; Pierson, Duane L.; Laughlin, Mitzi S.; Rezvani, Katayoun; Simpson, Richard J.
Abstract: Long-duration spaceflight impairs natural killer (NK) cell function, which could compromise immune surveillance in exploration class mission crew. To determine if microgravity can impair NK-cell function, we established a rotary cell culture system to expose human peripheral blood mononuclear cells to simulated microgravity (SMG) in vitro . We found that 12 h of SMG suppressed NK-cell cytotoxic activity (NKCA) by ~50% against K562, U266 and 721.221 tumor target cells when returned to the 1G environment. Mass cytometry was used to identify 37 individual markers associated with NK-cell activation, maturation and cytotoxicity, revealing that SMG causes reductions in NK-cell degranulation and effector cytokine production. Extended flow cytometry confirmed that SMG lowered NK cell perforin and granzyme b expression by 25% and 17% respectively, but did not affect the surface expression of various activating (NKG2D, NKp30) and inhibitory (NKG2A, KLRG1) receptors or the ability of NK-cells to conjugate with target cells. Flow cytometry further revealed that SMG impaired NK-cell degranulation (reduced CD107a+ expression) and suppressed TNFα and IFNγ secretion in response to stimulation with K562 target cells. These findings indicate that SMG 'disarms' human NK-cells of cytolytic granules and impairs NKCA against a range of tumor target cells in vitro . Exposure to microgravity could be a factor that contributes to impaired NK-cell function during long duration space travel. Highlights: Natural Killer cell function is impaired after simulated microgravity (SMG). Suppression of function without changes to phenotype. Decreased lysosomal degranulation and cytokine production after exposure to SMG. Leukemia(K562) susceptibility to killing doesn't change after SMG.